2019
DOI: 10.1371/journal.pone.0213224
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge gaps of STIs in Africa; Systematic review

Abstract: Sexually Transmitted Infections (STIs) are ambiguous burden of tremendous health, social and economic consequences. The current systematic review was conducted in order to determine awareness and knowledge of Africans toward sexually transmitted infections, not only concerning HIV/AIDS, but also other STIs such as gonorrhea, syphilis, HBV, HCV and HPV. A systematic review of literature was conducted, studies were retrieved and selected after fulfilling the inclusion criteria as well as passing the assessment p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 91 publications
1
24
0
Order By: Relevance
“…This is less important for adult women where HIV efficacy is more important. It is uncertain why adult women do not view STI protection as importantly as HIV protection when choosing between products, although it may be partly due to having less knowledge about STIs [61] and/or HIV being seen as a more serious disease than other STIs. It is also important that the full range of products are available to women for maximising uptake, with injectable ARV agents probably being most popular for adolescent and adult women.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…This is less important for adult women where HIV efficacy is more important. It is uncertain why adult women do not view STI protection as importantly as HIV protection when choosing between products, although it may be partly due to having less knowledge about STIs [61] and/or HIV being seen as a more serious disease than other STIs. It is also important that the full range of products are available to women for maximising uptake, with injectable ARV agents probably being most popular for adolescent and adult women.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Female participants showed a significantly higher mean of STDs-KS compared to males (8.51 ± 4.14 vs. 7.32 ± 4.38, p < 0.0001) (see Table 2, Figures 1 and 2). Median (interquartile range) for STDs-KS was 8 (5)(6)(7)(8)(9)(10)(11). Analysis indicates that the type of program in which the participant was registered, and gender, have a significant influence on the STDs-KS (p < 0.0001).…”
Section: Knowledge Of Sexually Transmitted Diseasementioning
confidence: 99%
“…Moreover, the World Health Organization emphasizes the value of knowledge and awareness of the population, as this promotes a drop in the rate of STD incidences and prevalence in the long-run [2]. Research indicates overall low levels of awareness and knowledge of STDs among people in Europe, Africa, and the Middle East; however, evidence from previous research suggests that the majority of people showed the highest awareness and knowledge of AIDS compared to another STDs [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Through several evidence-based strategies, such as ensuring community awareness on risks, prevention strategies, and treatment of STIs, this high burden of STIs and their effects are largely preventable. (2,4,13) The major components of Uganda's current strategy on STI management include primary prevention strategies such as vaccination, male circumcision, behavioral change interventions, and 'syndromic management, which involves the use of signs and symptoms rather than laboratory tests to guide treatment of STIs. (14) Despite these interventions, STIs are on an upward trend (8) and although the incidence is highest among young people, they have the least access to quality STI prevention and management services.…”
Section: Introductionmentioning
confidence: 99%